Disseminated Herpes Zoster in Elderly with Human Immunodeficiency Virus (HIV) Infection: A Case Report - Aurelia Stephanie; IGAA Elis Indira; Hermina Laksmi; Nevristia Pratama (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Disseminated herpes zoster (HZ) is one of the complications of HZ in the form of the appearance of the main lesion accompanied by the spread of solitary vesicles on the body. This condition occurs in 2% of the general population and 15-30% of immunodeficient patients, such as the elderly and HIV infection. Case presentation: A 64-year-old man came with the complaint of rashes all over his body four days ago. Vesicles and erosions are multiple in 1 dermatome and are discrete and scattered throughout the body on dermatological examination. The diagnosis of disseminated HZ, in this case, was established based on history, physical examination, and Tzank examination. HZ spread is less common and is characterized by the appearance of more than 20 vesicles or more than 2 consecutive dermatomes. Old age and HIV infection are immunocompromised conditions causing reactivation of the varicella-zoster virus and other infections. The patient received oral acyclovir, vitamins B1, B6, and B12, salicylic powder and topical fusidic acid, antiretrovirals (ARVs), azithromycin, intraoral cotrimoxazole, ceftriaxone, and intravenous fluconazole for 10 days. Skin lesions improved in 10 days without complications. Conclusion: Disseminated HZ in HIV patients should be considered because of complications, recurrence, more difficult with a treat, and a higher risk of acyclovir resistance.